A bibliometric approach to the analysis of the Technologically-Enhanced Language Learning (TELL) literature - Drakidou, Christina; Pareja-Lora, Antonio; Read, Timothy (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This paper presents a state-of-the-art research into three areas of TELL (Technologically-Enhanced Language Learning), namely Mobile-Assisted Language Learning (MALL), Language Massive Online Open Courses (LMOOCs), and Social and Open Language Learning (SOLL). In particular, the references from the Web of Science, Scopus and the UNED-Linceo+ meta-search engine discussed in Drakidou, Pareja-Lora & Read (2018), are analyzed here at a deeper level, in order to obtain some statistics on the languages taught, the countries with the most published papers, and the frequency of terms appearing in the keywords. Regarding the last one, the authors have aimed at identifying trends, tendencies and scarcities in all these three areas of TELL. Thus, this paper shows mainly the results of this bibliometric research, obtained in the second stage of the study.